Utilisation of rubber(Hevea brasiliensis)wood - Tisseverasinghe A E K (Ceylon Forester, 1970)
Rubber wood suffers the attack of biological wood deteriorating agents. Hence an effective preservation is essential for its wide utilisation. The simple diffusion treatment consists of momentary immersion of the fresh sawn wood in a hot (40 degree C), concentrated (25;) solution of a mixture of borax and boric acid mixed with sodium pentachlorophenate. The treated planks must be build in to stack and left undisturbed for three weeks. The end use restricted only for making indoor articles.
Keywords: Rubberwood